Brain mapping of emotional prosody in patients with drug-resistant temporal epilepsy: An indicator of plasticity. (August 2022) - Elizalde Acevedo, Bautista; Olano, María A.; Bendersky, Mariana; Kochen, Silvia; Agüero Vera, Valentina; Chambeaud, Nahuel; Gargiulo, Mercedes; Sabatte, Juliana; Gargiulo, Ángel; Alba-Ferrara, Lucía
Abstract: Introduction: Emotional prosody, a suprasegmental component of language, is predominantly processed by right temporo-frontal areas of the cerebral cortex. In temporal lobe epilepsy (TLE), brain disturbances affecting prosody processing frequently occur. This research assesses compensatory brain mechanisms of prosody processing in refractory TLE using fMRI. Methods: Patients with focal unilateral epilepsy, right (RTLE) (N = 19), left (LTLE) (N = 19), and healthy controls (CTRL) (N = 20) were evaluated during a prosody decoding fMRI task. The stimuli consisted in spoken numbers with different tones of voice (joy, fear, anger, neutral and silent trials). Participants were instructed to label the emotion with a keypad. "Joy" was removed from the analysis due to a high degree of variability. A lateralization index (LI) was used to see individual differences in the interhemispheric activations of each participant. Results: Behaviorally, The LTLE and RTLE groups did not differ significantly from each other neither from CTRL. In Negative Emotions versus Baseline contrast, the whole sample analysis showed extensive activations in bilateral superior temporal gyrus, bilateral precentral and post–central gyrus, right putamen, and left cerebellar vermis. Compared to the LTLE and CTRL, RTLE activated similar areas, but to a lesser extent. The LI analysis revealed significant differences in hemispheric laterality of the temporal lobe and the parietal lobe between RTLE compared to LTLE and CTRL, being the RTLE group lateralized towards the left, unlike the other two groups. Discussion: The LI indicated that, since the CTRL and the LTLE groups recruited putative prosodic regions, the RTLE lateralized prosody processing towards the left, recruiting contralateral nodes, homotopic to the putative areas of the prosody. Considering that the groups did not differ in prosody task performance, the findings suggest that, in the RTLE group, alternative brain nodes were recruited for the task, demonstrating plasticity.